Diseases of ear, nose, throat - Bansal, Mohan (New Delhi : Jaypee-Highligts Medical Publishers, 2013)
Guía completa para las enfermedades del oído, la nariz y la garganta, incluyendo el acceso gratuito en línea al banco de imágenes, MCQs y videos quirúrgicos
Comprehensive guide to diseases of the ear, nose and throat, including free online access to image bank, MCQs and surgical videos.
CONTENTS Section 1: Basic Sciences Anatomy and Physiology of Ear Section 2: Ear Section 3: Nose and Paranasal Sinuses Section 4: Oral Cavity and salivary glands Section : Pharynx and Esophagus y otros más...
Incluye índice
Incluye índice
Keywords: NARÍZ -- ENFERMEDADES; GARGANTA -- ENFERMEDADES; OÍDOS -- ENFERMEDADES; CABEZA -- ENFERMEDADES